2008
DOI: 10.1016/j.nuclcard.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Safety of regadenoson, an adenosine A2A receptor agonist for myocardial perfusion imaging, in mild asthma and moderate asthma patients: A randomized, double-blind, placebo-controlled trial

Abstract: In this pilot safety study of 48 patients with mild or moderate asthma who had bronchial reactivity to adenosine monophosphate, regadenoson was safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 14 publications
2
63
0
1
Order By: Relevance
“…Two small pilot studies of moderate to severe COPD and moderate asthma showed no statistically significant difference between regadenoson and placebo in bronchoconstrictive reactions as measured by spirometry. 32,33 While several other studies have examined the issue, 34 the only randomized study enrolled 999 patients with spirometry defined COPD or asthma and found no difference in the rate of bronchoconstriction between regadenoson and placebo, but did find more dyspnea. 35 …”
Section: Reactive Airway Diseasementioning
confidence: 99%
“…Two small pilot studies of moderate to severe COPD and moderate asthma showed no statistically significant difference between regadenoson and placebo in bronchoconstrictive reactions as measured by spirometry. 32,33 While several other studies have examined the issue, 34 the only randomized study enrolled 999 patients with spirometry defined COPD or asthma and found no difference in the rate of bronchoconstriction between regadenoson and placebo, but did find more dyspnea. 35 …”
Section: Reactive Airway Diseasementioning
confidence: 99%
“…4,35,39,40 Following initial post-marketing reports of wheezing, dyspnea, and respiratory arrest, 16 the use of regadenoson in patients with COPD and/or asthma was examined in randomized, double-blinded, cross-over, placebo-controlled trials that included patients with moderate-severe COPD (RegCOPD) and mild-moderate asthma (RegAsthma). 41,42 These showed that use of regadenoson in the above patient subgroups was well tolerated without significant changes in respiratory rate, FVC, FEV1, new-onset wheezing, or bronchoconstriction and oxygen saturation compared to placebo. 41,42 Of note, dyspnea was reported in 61% of patients in the regadenoson group vs 0% in the placebo group, this however, was not confirmed by objective measurements.…”
Section: Non-cardiovascular Adverse Effectsmentioning
confidence: 97%
“…[12][13][14][15] In two early, small, double-blind, placebo-controlled, crossover studies, regadenoson did not reduce forced expiratory volume in 1 second (FEV1) on serial pulmonary function testing or oxygen saturation as compared to placebo saline infusion. A more recent double-blind, randomized, placebo-controlled trial of 999 subjects (532 with asthma and 467 with COPD) evaluated the effects of regadenoson vs saline infusion using serial pulmonary function tests over a several-hour period postinjection.…”
Section: Regadenoson: a Selective A2a Adenosine Receptor Agonistmentioning
confidence: 99%